2004
DOI: 10.1021/ol048229x
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Promoted Payne Rearrangement of 3-CF3-2,3-Epoxyalcohols

Abstract: [reaction: see text] Smooth and selective Payne rearrangement was achieved for the above types of epoxyalcohols with a CF(3) group so as to form thermodynamically more stable alkoxides, where the strongly electron-withdrawing nature of this moiety played a significantly important role and was proved to overcome increased steric instability of epoxides from syn-E to anti-Z isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In summary, we have successfully demonstrated new pathways to access all stereoisomeric 2-amino-1,3-diol structures 9 with a CF 3 group starting from single materials, 3-CF 3 -2,3-epoxyketones 1 , by appropriate utilization of the characteristic nature of epoxyalcohols 2 accepting nucleophilic attack in a regiospecific manner only at the 3 position with complete inversion of stereochemistry. Moreover, following an electronically driven Payne rearrangement we have already reported previously, conversion of 3 to the corresponding carbamates 10 allowed selective cyclization to the oxazolidinone ring, which unambiguously determined the stereochemistry of the products 11 and 12 whose ring structure was found to be easily opened by treatment of an ethanolic alkalinesolution in excellent yields. As summarized below, a combination of these methods enabled us to readily synthesize 2-amino-1,3-diols in a stereodivergent fashion within 5 facile steps, and further application of this strategy is underway in this laboratory.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…In summary, we have successfully demonstrated new pathways to access all stereoisomeric 2-amino-1,3-diol structures 9 with a CF 3 group starting from single materials, 3-CF 3 -2,3-epoxyketones 1 , by appropriate utilization of the characteristic nature of epoxyalcohols 2 accepting nucleophilic attack in a regiospecific manner only at the 3 position with complete inversion of stereochemistry. Moreover, following an electronically driven Payne rearrangement we have already reported previously, conversion of 3 to the corresponding carbamates 10 allowed selective cyclization to the oxazolidinone ring, which unambiguously determined the stereochemistry of the products 11 and 12 whose ring structure was found to be easily opened by treatment of an ethanolic alkalinesolution in excellent yields. As summarized below, a combination of these methods enabled us to readily synthesize 2-amino-1,3-diols in a stereodivergent fashion within 5 facile steps, and further application of this strategy is underway in this laboratory.…”
mentioning
confidence: 52%
“…We have previously reported Payne rearrangement of CF 3 -containing epoxyalcohols E - syn - 2 and E - anti - 2 specifically to Z - anti - 3 and E - anti - 3 , respectively, whose driving force was, from the computational point of view, considered to be the thermodynamic preference of the corresponding alkoxide ion stabilized by a strongly electron-withdrawing CF 3 group (Scheme ). It is well-known that nucleophilic attack at the CF 3 -attached carbon atom is usually restricted , as a result of the electrostatic characteristics of this group rendering the F 3 C- C−O bond shorter (thus stronger), and nucleophiles approach from the backside of this bond with difficulty.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 While studying the Payne rearrangement Yamazaki et al reported the use of Red-Al ® for the regioselective opening of an epoxy alcohol to furnish a 1,3-diol. 13 (H) Corey et al reported the transformation shown; the regioselectivity of reduction could be controlled by the addition of a base. Other hydride reagents, such as NaBH 4 , LiBH 4 , L-selectride, and 9-BBN-H were unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously disclosed the synthetic pathway to ketones 2 by successive Red-Al reduction of 1a , followed by PDC oxidation (Scheme ). However, the first step, conversion of propargylic alcohols 1 to the corresponding allylic counterparts 3 , sometimes suffered from overreduction of the desired 3 to the difluorinated homoallylic alcohols 4 , and separation of these two compounds was a quite troublesome task . While our above-mentioned process shown in Scheme (EWG = CF 3 ) is recognized as the alternative protocol to 2 , quite unfortunately, this technique is applicable to only the case for R = Ar as mentioned above.…”
mentioning
confidence: 99%